2016
DOI: 10.1021/acsmedchemlett.6b00014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potent and Selective GPR4 Antagonist as a Drug Lead for the Treatment of Myocardial Infarction

Abstract: GPR4, a pH-sensing G protein-coupled receptor, is highly expressed in endothelial cells and may be activated in myocardial infarction due the decreased tissue pH. We are interested in GPR4 antagonists as potential effective pharmacologic tools and/or drug leads for the treatment of myocardial infarction. We investigated the structure−activity relationship of a known GPR4 antagonist 1 as a lead compound to identify 3b as the first potent and selective GPR4 antagonist, whose effectiveness was demonstrated in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 10 publications
(22 reference statements)
2
63
0
Order By: Relevance
“…Other similar GPR4 inhibitors have also been shown to reduce acidosis-induced EC inflammation and promote survival in a mouse myocardial infarction model [21,23]. We aimed to use the GPR4 inhibitor (EIDIP) to study the acidosis-induced endothelial ER stress/UPR effects.…”
Section: Resultsmentioning
confidence: 99%
“…Other similar GPR4 inhibitors have also been shown to reduce acidosis-induced EC inflammation and promote survival in a mouse myocardial infarction model [21,23]. We aimed to use the GPR4 inhibitor (EIDIP) to study the acidosis-induced endothelial ER stress/UPR effects.…”
Section: Resultsmentioning
confidence: 99%
“…Use of GPR4 inhibitors could prove as a valuable tool to inhibit inflammation by reducing leukocyte recruitment and adhesion to inflamed tissues. Recently, our group and others have demonstrated the effectiveness of the GPR4 inhibitors in the selective targeting of GPR4 and inhibition of GPR4 target gene expression [15, 17, 73]. Additionally, GPR4 antagonists have been used in vivo and no obvious toxicities have been reported [18, 73].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group and others have demonstrated the effectiveness of the GPR4 inhibitors in the selective targeting of GPR4 and inhibition of GPR4 target gene expression [15, 17, 73]. Additionally, GPR4 antagonists have been used in vivo and no obvious toxicities have been reported [18, 73]. A recent study showed that GPR4 antagonists provided therapeutic benefits in a myocardial infarction mouse model [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR4 inhibitors have proved effective in the reduction of endothelial inflammation and subsequent tissue inflammation in vitro and in vivo Dong et al, 2013;Fukuda et al, 2016;Hosford et al, 2018;Miltz et al, 2017;Tobo et al, 2015;Velcicky et al, 2017). A group of imidazo-pyridine and pyrazolopyrimidine derivatives were previously found to elicit inhibitory effects on GPR4-mediated EC activation Dong et al, 2013;Hosford et al, 2018;Miltz et al, 2017;Tobo et al, 2015;Velcicky et al, 2017).…”
Section: Discussionmentioning
confidence: 99%